Natural Resource-Based Food Supply Chain in Development of the Masela Block - Maryam Sangadji; Muspida; Lussi R Loppies (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study aims to examine the supply chain for food needs based on the natural resources of the Tanimbar Islands in the face of Masela Block development The availability of components for distributors, cooperatives / Village-Owned Enterprises (BUMDES), farmer producers, home industries, inter-island traders, supermarkets/markets / retail and the Regional Investment Coordinating Board (BKPMD) has not yet become the main component of the supply chain system for meeting food needs principal The study was conducted with a qualitative approach, using a sample area of sub-districts and villages by "purposive sampling". The data were analyzed descriptively, and to determine the model and strategy of sustainable supply chain development, a SWOT analysis was used This paper provides a theoretical contribution to the concept of developing and utilizing distributor components through a potential study of each element. The results showed that for food needs in facing the Masela Block, it is predicted that by 2035 there will be a surplus or deficit in certain food commodities. The production facilities, transportation, and post-harvest processing services group can support businesses in agriculture, livestock and fisheries. Meanwhile, those who can supply staple food are transportation, warehousing, sales services, and labour services. The distributors, cooperatives / Village-Owned Enterprises (BUMDES), farmer producers, home industries, inter-island traders, supermarkets/markets / retail and the Regional Investment Coordinating Board (BKPMD) are the main components of the ideal supply chain system for basic food needs. Local governments must further improve their ability to build distributor networks and have a sustainable and public accountability system or public accountability by prioritizing public service standards Researchers can then develop research studies to find operational mechanisms for the relationship between components and a formal accountability model in realizing component governance that benefits local actors and local governments. This research has had an impact on innovation in structuring the supply chain for sustainable staple food needs. The government must be able to encourage changes in chain management and the dominant control over supply chains in the regions Future research should focus on managing the ideal supply chain for sustainable staple food to face the Masela Block project by developing mutually beneficial business partnerships, from upstream to downstream.